(untitled) (Comparative & International Education Series, 2021)
Historically Black colleges and universities are equipped to facilitate study abroad in Black students and short-term study abroad opportunities provide an affordable and appealing alternative to semester abroad programs. This short-term, faculty-led, study abroad program was developed to promote study abroad in Black students at an HBCU in Baltimore, Maryland. This program has been shown to be feasible in HBCU students and have a significant positive impact on students in several areas of global enrichment. This program may serve as a platform for other instructors and universities to develop more study abroad opportunities for students that are more feasible than the traditional semester abroad.